Enhancing Vocational Students Graphic Design Competence for Interactive Social Media Content Creation - Lusyani Sunarya; Richard Andre Sunarjo; Marviola Hardini; Mamih Maya Pebiyanti; Maulana Abbas; Wahyu Nur Wahid; Bintang Nandana Henry (ADI Pengabdian Kepada Masyarakat, 2025)
The rapid development of digital technology in the era of the Industrial Revolution 4.0 has compelled the education sector, particularly vocational schools (SMK), to produce graduates who are creative, adaptive, and competent in the creative industry. One crucial competency is graphic design skills, which play an essential role in digital content production and visual communication. This community service activity was conducted at SMK Ki Hajar Dewantoro, Tangerang City, aiming to enhance the competence of students majoring in Visual Communication Design (DKV) in mastering graphic design and creating interactive social media content. This program is an implementation of the 2025 Community-Based Empowerment Funding Program, approved by the Directorate General of Research and Development, Ministry of Higher Education, Science, and Technology. The method employed was Project-Based Learning (PBL), which focuses on improving students’ technical, creative, and collaborative skills through real project-based learning. The activity consisted of five stage socialization, training in design software (Adobe Photoshop and Illustrator), mentoring in digital content creation, evaluation of outcomes, and program sustainability planning. The results indicated a significant improvement in students’ technical abilities and creativity in producing visual designs, resulting in attractive and functional products such as posters and die-cut packaging. This program contributes to the achievement of SDGs 4 (Quality Education) and SDGs 9 (Industry, Innovation, and Infrastructure), and aligns with Asta Cita 7 and Asta Cita 8 in strengthening digital skills and national self-reliance. This activity serves as a best-practice model of community service that effectively enhances vocational competence in the modern learning era.